2000
DOI: 10.2307/1592530
|View full text |Cite
|
Sign up to set email alerts
|

Avian Pneumovirus Infection in Minnesota Turkeys: Experimental Reproduction of the Disease

Abstract: Avian pneumovirus (APV) is an emerging viral respiratory disease agent of turkeys in Minnesota. Clinical signs of APV infection include open mouth breathing, ocular and nasal discharge, and swelling of infraorbital sinuses. The virus spreads rapidly among flocks of susceptible turkeys and is associated with increased mortality rates. A flock of 11-wk-old turkeys experienced a respiratory problem characterized by coughing, sneezing, swollen sinuses, and nasal discharge. The reverse transcriptase-polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2000
2000
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…Cytoplasmic eosinophilic inclusions and polykaryocytes have also been reported (Giraud et al, 1986). After adaptation to cell culture, syncytial formation may be seen within a few days of inoculation (Jirjis et al, 2000). The CPE in VEROs, which is similar to that seen in various avian cell cultures, is initially characterized by the appearance after about 5 days of scattered focal areas of cell rounding.…”
Section: Systems Available and Their Limitationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Cytoplasmic eosinophilic inclusions and polykaryocytes have also been reported (Giraud et al, 1986). After adaptation to cell culture, syncytial formation may be seen within a few days of inoculation (Jirjis et al, 2000). The CPE in VEROs, which is similar to that seen in various avian cell cultures, is initially characterized by the appearance after about 5 days of scattered focal areas of cell rounding.…”
Section: Systems Available and Their Limitationsmentioning
confidence: 64%
“…Although the isolation of APV in CEF cultures from experimentally infected turkeys has been reported (Jirjis et al, 2000), there is little evidence to suggest that this is a sensitive method and many passages are apparently required before the virus is successfully isolated. This increases the risk of laboratory contamination.…”
Section: Systems Available and Their Limitationsmentioning
confidence: 99%
“…Sham-inoculated birds from both trials were similarly challenged with turkey 2a/97. The turkey 2a/97 isolate was previously shown to induce clinical signs in susceptible turkeys (13). The virulent-challenge model involved using bacterial coinfection to enhance the clinical signs of turkey 2a/97 aMPV infection.…”
Section: Methodsmentioning
confidence: 99%
“…Metapneumoviruses have an enveloped virion containing a single-stranded, negative-sense RNA genome consisting of eight genes, with their products organized in the order 3Ј-N-P-M-F-M2-SH-G-L-5Ј, with a total length of between 13,134 (aMPV subtype C [aMPV/C]) and 13,378 (hMPV) nucleotides (12,27). The aMPV strains isolated from the United States were a distinct subtype C, genetically different from the subtypes A (aMPV/A), B (aMPV/B), and D (aMPV/D) circulating in Europe, Asia, Africa, and South America (2,22,23,24,34,38,46,47,48).…”
mentioning
confidence: 99%
“…Avian pneumovirus (APV) is an emerging respiratory viral pathogen in turkeys, causing severe economic loss to the turkey industry in the United States (2,5,7,8). Studies in our laboratories and by others have shown that APV isolates from the United States differ genetically and antigenically from the European A and B subtypes of APV and have therefore been designated subgroup C APV (APV/US) (3,9,10,12,13).…”
mentioning
confidence: 99%